Influence of Initial Contact Geometry on Mechanical Properties in Friction Welding of Dissimilar Materials Aluminum 6351 T6 and SAE 1020 Steel - Marlon A. Pinheiro; Alexandre Q. Bracarense (Advances in Materials Science and Engineering)
Friction welding is a solid-state bonding process that presents itself as an interesting option as it generates less residual stress, less distortion, and crack formation when compared to the fusion welding process. The characteristics of this process also allow satisfactory welding of dissimilar materials, with good results in terms of mechanical strength. In this work, the butt welding of aluminum ASTM A6351-T6 and SAE 1020 steel was carried out aiming at evaluating the effects of the initial contact geometry on the mechanical properties of the welded joint. The methodology consisted of friction weld aluminum bars with different initial contact geometry with steel bars in a machine specially developed for the application. The results indicated the influence of this parameter on the mechanical properties of the welded joint.